THE IMPACT OF KIDNAPPING ON HUMAN SECURITY IN ETHIOPIA: A CASE STUDY OF TACH ARMACHIHO WOREDA IN THE CENTRAL GONDAR ADMINISTRATIVE ZONE - SETEGN ABUHAY MOLA (Innovare Journal of Social Sciences, 2025)
The objective of this study was to investigate the overall impacts of kidnapping on human security in the case of Tach Armachiho Woreda, CentralGondar Administrative Zone. More specifically, this study attempted to identify the actors involved in kidnapping and examined the impacts of kidnapping on human security. In doing so, the researcher employed a mixed approach, followed by questionnaires, semi-structured interviews, and document analysis as instruments of data collection. In this study, a sequential exploratory design was utilized. The results of the study showed that local bandits, unemployed youth, security agents, and agents of local bandits were the main actors in kidnapping in the study area. Overall, the economic motive is the main driving factor of kidnapping. Kidnapping is a major threat to the communities. Victims are tortured by kidnappers after kidnapping; if they do not pay a ransom, the hostages are killed. As confirmed by the respondents, the rural part of the Woreda is more vulnerable to kidnapping. The findings indicated that kidnapping poses a serious threat to the people of the Amhara regional state, psychologically, socially, economically, and politically. As confirmed by the majority of respondents, religious institutions and elders create awareness in the community in a better manner than other stakeholders. Hence, governmental and non-governmental institutions in collaboration should create awareness to the local community especially; the society should be hand in glove with the security agents and administration wing of the region also take immediate measures against offenders are the recommendation of this study.